Transposition of the great arteries: the importance of new strategies for rapid diagnosis - de França, Daniella Acioli Lima; Granja, Ana Julia Peixoto; de Melo, Gabriel Cavalcante Calheiros; Leandro, Paulo Arthur Cavalcante; Soares, João Victor da Silva; Nunes, Isabella Cristina Farias; Brandão, Isabelle Ataíde Correia Lima; Grossl, Fernanda de Almeida Amaral; Ferreira, Wanessa do Carmo (Seven Editora, 2023)
Transposition of the Great Arteries (TGA) is considered the predominant cyanotic congenital heart disease (CHD) of the neonatal period, accounting for 5-9% of cardiac malformations. In TGA, the ventriculo-arterial connection is considered discordant, as the ascending aorta arises abnormally from the morphological right ventricle and the pulmonary artery arises abnormally from the morphological left ventricle, connected to the pulmonary trunk (YELBUZ et al., 2018). Therefore, the systemic and pulmonary circulations are in parallel rather than in series, causing oxygen-poor blood to circulate through the body and oxygenated blood to circulate through the lungs (SÉGUÉLA et al., 2016). DOI: https://doi.org/10.56238/colleinternhealthscienv1-075